Cryopreservation of Platelet Concentrates in Combined Preservatives at Different Temperature Regimens (–70…–80 and –196°C) - Korobkova, Anna V.; Kompaniets, Antonina M. (Problems of Cryobiology and Cryomedicine, 2014)
N/A Probl Cryobiol Cryomed 2014; 24(2):162.